In vitro inhibition of human UGT isoforms by ritonavir and cobicistat - Algeelani, Sara; Mikus, Gerd (Xenobiotica, 2017)
1. Ritonavir and cobicistat are pharmacokinetic boosting agents used to increase systemic exposure to other antiretroviral therapies. The manufacturer's data suggests that cobicistat is a more selective CYP3A4 inhibitor than ritonavir. However, the inhibitory effect of ritonavir and cobicistat on human UDP glucuronosyltransferase (UGT) enzymes in Phase II metabolism is not established. This study evaluated the inhibition of human UGT isoforms by ritonavir versus cobicistat. 2. Acetaminophen and ibuprofen were used as substrates to evaluate the metabolic activity of the principal human UGTs. Metabolite formation rates were determined by HPLC analysis of incubates following in vitro incubation of index substrates with human liver microsomes (HLMs) at different concentrations of ritonavir or cobicistat. Probenecid and estradiol served as positive control inhibitors. 3. The 50% inhibitory concentrations (IC50) of cobicistat and ritonavir were at least 50 µM, which substantially exceeds usual clinical plasma concentrations. Probenecid inhibited the glucuronidation of acetaminophen (IC50 0.7 mM), but not glucuronidation of ibuprofen. At relatively high concentrations, estradiol inhibited ibuprofen glucuronidation (IC50 17 µM). 4. Ritonavir and cobicistat are unlikely to produce clinically important drug interactions involving drugs metabolized to glucuronide conjugates by UGT1A1, 1A3, 1A6, 1A9, 2B4 and 2B7.
Gesehen am 24.04.2018